2007
DOI: 10.1111/j.1365-2222.2007.02818.x
|View full text |Cite
|
Sign up to set email alerts
|

Do levels of airborne grass pollen influence asthma hospital admissions?

Abstract: Our findings suggest that grass pollen levels influence asthma hospital admissions. High grass pollen days, currently defined as more than 50 grains/m3, are days when most sensitive individuals will experience allergic symptoms. However, some asthmatic patients may be at a significant risk even when airborne grass pollen levels are below this level. Patients with pollen allergies and asthma would be advised to take additional preventive medication at lower ambient concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
67
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 33 publications
7
67
0
1
Order By: Relevance
“…In Croatia, Hungary and Serbia, the threshold value amounts to 30 APG/ m 3 [16,36], whereas in Spain the first allergy symptoms were observed at 25 APG/m 3 [62]. For children and adolescents from Malmö (Sweden), nose symptom scores increased continuously and linearly with pollen counts from concentrations of 0-30 APG/m 3 , wherefrom symptom severity [64] demonstrated that a concentration of 30 APG/m 3 was sufficient to induce symptoms in most grass-allergic asthmatics in Melbourne, Australia. De Weger et al [65] found that Poaceae pollen allergic patients have more severe symptoms in the early season compared to the late season at similar concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In Croatia, Hungary and Serbia, the threshold value amounts to 30 APG/ m 3 [16,36], whereas in Spain the first allergy symptoms were observed at 25 APG/m 3 [62]. For children and adolescents from Malmö (Sweden), nose symptom scores increased continuously and linearly with pollen counts from concentrations of 0-30 APG/m 3 , wherefrom symptom severity [64] demonstrated that a concentration of 30 APG/m 3 was sufficient to induce symptoms in most grass-allergic asthmatics in Melbourne, Australia. De Weger et al [65] found that Poaceae pollen allergic patients have more severe symptoms in the early season compared to the late season at similar concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Such results indicate that A. catechu pollen is an important aeroallergen with a significant contribution to IgE-mediated hypersensitivity and emergency asthma hospitalization. In Melbourne, it was found that the grass pollen count had a significant effect on asthma hospitalization up to a threshold of 30 grains/m 3 of air [24]. Similarly, a significant increase in daily asthma emergency admission was recorded for airborne tree pollens like Ulmas, Pinaceae members, Tsuga, Larix, Quercus, Castanea, Acer and others [25].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have focused on the most severe episodes, although there may be an aggravation of symptoms without needing emergency care. The relationship between effects and aeroallergen levels could be nonlinear (Tobias et al 2004;Erbas et al 2007), whereas some authors have looked for linear effects only. The study period was not always limited to the period of pollen or spore dispersal.…”
Section: Chemical and Biological Weathermentioning
confidence: 99%